1996
DOI: 10.1063/1.471921
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulation of a chloride ion in water under the influence of an external electric field

Abstract: Molecular dynamics simulations were performed for one chloride ion in 213 water molecules under various applied external electrical fields. The field strength varied from 0.5–2⋅1010 V/m. The structure of the solution is described by various radial distribution functions, hydrogen bond statistics, and the deviation from tetrahedrality. The selfdiffusion coefficients and the spectral densities of the hindered translational motions of the water molecules have been calculated from the velocity autocorrelation func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
43
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 10 publications
11
43
0
Order By: Relevance
“…Similar trends have been observed earlier also in related simulation studies, although the absolute magnitudes differ. Sutmann, 16 for example, showed that ͗n HB ͘ increases from ϳ2.03 at zero field to ϳ2.73 at 4 ϫ 10 10 V / m. Similarly, Kiselev and Heinzinger 15 showed that ͗n HB ͘ increases from ϳ2.7 at zero field to ϳ3.1 at 2 ϫ 10 10 V / m. It may be noted that the zerofield value of ͗n HB ͘ predicted by both these simulation approaches are not in agreement with those reported elsewhere ͑see …”
Section: -6mentioning
confidence: 99%
See 1 more Smart Citation
“…Similar trends have been observed earlier also in related simulation studies, although the absolute magnitudes differ. Sutmann, 16 for example, showed that ͗n HB ͘ increases from ϳ2.03 at zero field to ϳ2.73 at 4 ϫ 10 10 V / m. Similarly, Kiselev and Heinzinger 15 showed that ͗n HB ͘ increases from ϳ2.7 at zero field to ϳ3.1 at 2 ϫ 10 10 V / m. It may be noted that the zerofield value of ͗n HB ͘ predicted by both these simulation approaches are not in agreement with those reported elsewhere ͑see …”
Section: -6mentioning
confidence: 99%
“…Alper and Levy 14 observed large nonlinear effects associated with molecular polarization between ϳ1 ϫ 10 9 and ϳ2 ϫ 10 10 V / m. Kiselev and Heinzinger 15 observed a monotonic increase in the average number of H-bonds per molecule as the field strength was increased from 0 to 2 ϫ 10 10 V / m. Sutmann 16 obtained a similar result up to a field strength of 4 ϫ 10 10 V / m. They also observed a phase transition into an ordered, icelike structure stabilized through H-bonds at a field strength of ϳ3 ϫ 10 10 V / m. Using a different molecular model, Yeh and Berkowitz 17 found a similar phase transition to take place at a lower field strength of ϳ10 10 V/m.…”
Section: Introductionmentioning
confidence: 99%
“…The application of an external field to bulk water under ambient conditions by Heinzinger et al 15 did not produce any observable structural transformation, except for the strongest of the fields (10 8 V/cm), where a long-range order in the oxygen-oxygen radial distribution functions was detected. No tendency for crystallization, but an overall enhancement of the hydrogen-bonding network has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…A more hydrogenbonded network structure slows reactions due to its increased viscosity, reduced diffusivity, and the less active participation of water molecules. The application of external load ͑pressure͒, [1][2][3][4][5][6][7][8][9] of electric field, [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] of ultrasound flow, 25 or the confinement of water thin films between plates or within cylindrical pores 26,27 results in the break-up of the hydrogenbonding network and under certain conditions, the induction of a phase transition between different water forms. These effects remain largely unexplored despite the significance this knowledge has for understanding the solvation behavior and properties of water in biological systems.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was possible to produce ice cubic structures in molecular dynamics ͑MD͒ simulations [2][3][4][5][6][7][8][9][10][11][12][13] by applying a rather strong electric field on supercooled liquid water. Although this transformation in bulk water and in Stockmayer fluids 14,15 has been studied in some detail, mainly from the structural point of view, the precise route to crystallization with increasing field strength and the concomitant change in dynamics has not been given equal attention.…”
Section: Introductionmentioning
confidence: 99%